Philosophical antinomies in painting: Vermeer and Friedrich - Noel Lapoujade, María (2025)
As stated by Leonardo's epigraph, the fundamental premise in this paper is that, just like painting is philosophy, philosophy is painting as well. Just like painting expresses different philosophical problems, philosophy can be concretely applied in painting. Drawing from this premise, the purpose of this paper is to demonstrate that the paintings by Jan Vermeer and Caspar Friedrich are a fertile field for the formulation of certain conceptual, abstract antinomies through pictoric images. On the other hand, literature has expressed –and exceeded– the magnificence of painting through memorable poems and poetic prose. In this regard, I refer particularly to Wolfgang Goethe, Rainer-María-Rilke, Marcel Proust and Giusseppe Ungaretti. Our approach is thus interdisciplinary. The integration of painting, music, literature and philosophy helps us to highlight the concrete universality of the works of art, as parts in a living texture.